High and low frequency stimulation of the subthalamic nucleus induce prolonged changes in subthalamic and globus pallidus neurons - Lavian, Hagar; Ben-Porat, Hana; Korngreen, Alon (Frontiers in Systems Neuroscience, 2013)
High frequency stimulation (HFS) of the subthalamic nucleus (STN) is widely used to treat the symptoms of Parkinson’s disease but the mechanism of this therapy is unclear. Using a rat brain slice preparation maintaining the connectivity between the STN and one of its target nuclei, the globus pallidus (GP), we investigated the effects of high and low frequency stimulation (HFS 100 Hz, LFS 10 Hz) on activity of single neurons in the STN and GP. Both HFS and LFS caused changes in firing frequency and pattern of subthalamic and pallidal neurons. These changes were of synaptic origin, as they were abolished by glutamate and GABA antagonists. Both HFS and LFS also induced a long-lasting reduction in firing frequency in STN neurons possibly contending a direct causal link between HFS and the outcome DBS. In the GP both HFS and LFS induced either a long-lasting depression, or less frequently, a long-lasting excitation. Thus, in addition to the intrinsic activation of the stimulated neurons, long-lasting stimulation of the STN may trigger prolonged biochemical processes.